Arguing about knowledge - Neta, Ram; Pritchard, Duncan (Arguing about philosophy., 2009)
What is knowledge? What are the sources of knowledge? What is the value of knowledge? What can we know? Arguing About Knowledge offers a fresh and engaging perspective on the theory of knowledge. This comprehensive and imaginative selection of readings examines the subject in an unorthodox and entertaining manner whilst covering the fundamentals of the theory of knowledge. It includes classic and contemporary pieces from the most influential philosophers from Descartes, Russell, Quine and G.E. Moore to Richard Feldman, Edward Craig, Gilbert Harman and Roderick Chisholm. In addition, students will find fascinating alternative pieces from literary and popular work such as Lewis Caroll, Jorges Luis Borges and Paul Boghossian. Each article selected is clear, interesting and free from unnecessary jargon. The editors provide lucid introductions to each section in which they give an overview of the debate and outline the arguments of the papers. Arguing About Knowledge is an inventive and stimulating reader for students new to the theory of knowledge.